Cyber-Attacks and the Exploitable Imperfections of International Law. - Radziwill, Yaroslav (Brill, 2015)
Cyber-Attacks and the Exploitable Imperfections of International Law reveals elements of existing jus ad bellum and jus in bello regimes that are unable to accommodate the threats posed by cyber-attacks. It maps out legal gaps, deficiencies, and uncertainties, which international actors may seek to exploit to their political benefit.